IL‐1β Is an Androgen‐Responsive Target in Macrophages for Immunotherapy of Prostate Cancer - Deng Wang; Chaping Cheng; Xinyu Chen; Jinming Wang; Kaiyuan Liu; Na Jing; Penghui Xu; Xialian Xi; Yujiao Sun; Zhongzhong Ji; Huifang Zhao; Yuman He; et al. (Advanced Science, 2023)
Abstract Great attention is paid to the role of androgen receptor (AR) as a central transcriptional factor in driving the growth of prostate cancer (PCa) epithelial cells. However, the understanding of the role of androgen in PCa‐infiltrated immune cells and the impact of androgen deprivation therapy (ADT), the first‐line treatment for advanced PCa, on the PCa immune microenvironment remains limited. On the other hand, immune checkpoint blockade has revolutionized the treatment of certain cancer types, but fails to achieve any benefit in advanced PCa, due to an immune suppressive environment. In this study, it is reported that AR signaling pathway is evidently activated in tumor‐associated macrophages (TAMs) of PCa both in mice and humans. AR acts as a transcriptional repressor for IL1B in TAMs. ADT releases the restraint of AR on IL1B and therefore leads to an excessive expression and secretion of IL‐1β in TAMs. IL‐1β induces myeloid‐derived suppressor cells (MDSCs) accumulation that inhibits the activation of cytotoxic T cells, leading to the immune suppressive microenvironment. Critically, anti‐IL‐1β antibody coupled with ADT and the immune checkpoint inhibitor anti‐PD‐1 antibody exerts a stronger anticancer effect on PCa following castration. Together, IL‐1β is an important androgen‐responsive immunotherapeutic target for advanced PCa.